2021
DOI: 10.1055/a-1308-1297
|View full text |Cite
|
Sign up to set email alerts
|

Colon capsule endoscopy in colorectal cancer screening: a systematic review

Abstract: Introduction Primary colonoscopy and fecal immunochemical test (FIT) are the most commonly used colorectal cancer (CRC) screening modalities. Colon capsule endoscopy (CCE) might be an alternative. Data on the performance of CCE as a CRC screening tool in a screening population remain scarce. This is the first systematic review to provide an overview of the applicability of CCE as a CRC screening tool. Methods A systematic search was conducted of literature published up to September 2020. Studies repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 28 publications
1
56
0
1
Order By: Relevance
“…However, adjustments to the procedures will be pursued. The completion rate was lower than in previous studies 11 12 13 14 , although in line with results from other screening populations 4 15 and with a conclusive investigation rate of 80.3 %. The PDR was 73.5 %, whereas in the national CRC screening program, the adenoma detection rate (ADR) is 49 %.…”
Section: Discussionsupporting
confidence: 86%
“…However, adjustments to the procedures will be pursued. The completion rate was lower than in previous studies 11 12 13 14 , although in line with results from other screening populations 4 15 and with a conclusive investigation rate of 80.3 %. The PDR was 73.5 %, whereas in the national CRC screening program, the adenoma detection rate (ADR) is 49 %.…”
Section: Discussionsupporting
confidence: 86%
“…Both capsule endoscopy 47 and computed tomography (CT) colonography 48,49 have been reported to have high sensitivity and specificity for lesions > 10mm (including adenomas) in Japanese studies. However, since it is not possible to perform a pathological evaluation at the same time, these tests are not recommended for screening, except for patients with ileocaecal adhesions/organic anomalies or comorbidities 50,51 (see the text for 'recommendation 2a' below and Table 1). Endoscopic techniques for the management of early colon cancer are discussed in detail in the Asian guidelines.…”
Section: Screening Principles -Recommendations 1a-fmentioning
confidence: 99%
“…Stool-based DNA testing is one such modality which, when compared to OC as the reference standard in the DeeP-C cross-sectional study, was found to have sensitivity and specificity rates of 92.3% and 86.6%, respectively, for detecting CRC. Despite CCE having a comparable CRC detection of 93%, its potential drawback as a screening tool in CRC detection lies within the need for bowel preparation and variable completion rates [ 3 , 37 ].…”
Section: Polyp Detection and Size Estimationmentioning
confidence: 99%
“…One such strategy to visualize the colon is by means of colon capsule endoscopy (CCE), which allows for a pain-free colonic assessment by eliminating the need for instrument insertion, gas insufflation or sedation [ 1 , 2 ]. This has allowed for the extension of CCE’s role in colorectal cancer (CRC) screening in the average-risk population, as well as an alternative for patients who refuse optical colonoscopy (OC) or in whom the latter is contraindicated [ 3 , 4 , 5 ]. Although CT colonography (CTC), like CCE, can visualise the colon without biopsy or therapy capabilities, in CTC, gas insufflation is required while concerns remain as to the ”allowed” frequency of use due to radiation exposure.…”
Section: Introductionmentioning
confidence: 99%